Statistical (SPSS) Models: Ultimate Uplift Capacity of Horizontal Square Anchor Plate - Daibil, Ali R.; Al-Saidi, A’amal A. H. (Civil Engineering Journal, 2025)
This paper examines the relationship between ultimate capacity and vertical displacement for single anchors and line anchor groups (1×2), (1×3), (1×4), and (1×5), in relation to the number of anchors and the embedment depth. Studies addressing statistical analysis in this area are limited; therefore, it was considered appropriate to conduct a statistical investigation to support this field with analytical results and to provide a foundation for future research. The statistical analysis for the single anchor plate indicated that the correlation between ultimate capacity, number of anchors, and embedment depth was strong, with acceptable values of R and R² and a well-fitting mathematical model. In contrast, vertical displacement showed insufficient mathematical representation when analyzed against the number of anchors and embedment depth, as vertical displacement is influenced by additional factors such as loading duration (creep effects), soil unit weight, plate shape and dimensions, internal friction angle, and moisture content, rather than by ultimate capacity alone. When the number of anchor plates in a group exceeds three, the vertical displacement at system failure increases due to the reduced strength of the soil associated with larger anchor groups.